Release of Contractures by Subcutaneous Pedicled Rhomboid Flaps - Mannan, II; Khundkar, SH; Ahmed, T; Ibrahim, FB (Bangladesh Journal of Plastic Surgery, 2013)
The subcutaneous pedicled rhomboid flap is a technique that can release scar contractures without skin graft or additional flap. This study was planned to evaluate the efficacy of this technique. This prospective interventional study was conducted in the department of Plastic Surgery, Dhaka Medical College Hospital, over a period of 16 months. A total of 28 procedures of subcutaneous pedicled rhomboid flap were performed on 12 patients. The contractures were released successfully by the rhomboid flaps. The mean percentage gain in length of the scar band was 77.28%. Most of the cases had complication free recovery. The clinical results indicated that the subcutaneous pedicled rhomboid flap is an effective and versatile technique for releasing scar contractures in different parts of the body. DOI: http://dx.doi.org/10.3329/bdjps.v3i1.14998 Bangladesh Journal of Plastic Surgery 2012, 3(1): 3-6